Meta Analysis: Factors Affecting Implementation of Self-Care Practice in Diabetes Mellitus Patients - Khairiyyah, Alimah Ulfah; Nazalah, Rajba; Aditya, Stefanus; Murti, Bhisma; Marsim, Etanaulia (Indonesian Journal of Medicine, 2024)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by high blood sugar levels. If not controlled properly, diabetes mellitus can cause serious complications. Self-care practices are a very important factor in controlling the disease. This study aims to estimate the factors that influence self-care practices in diabetes sufferers.Subjects and Method: This was a systematic review and meta-analysis using PICO format. Population: diabetes patients. Intervention: having diabetes knowledge, high social support, female gender and presence of comorbidities. Comparison: no diabetes knowledge, low social support, male gender and no comorbidities. Outcome: self-care practices. The articles used in this research came from 5 databases, namely Google Scholar and Science Direct. The keywords of the article are "Diabetes Knowledge" AND "Social Support" AND "gender" AND "comorbidities" AND "diabetes" AND "Self-care practice behavior". The articles included in this research are full paper articles, cross-sectional study, publication year range 20172023, and reporting the aORs. Articles were analyzed using the Review Manager 5.4.Results: Female patients (aOR=1.56; 95% CI= 1.04 to 2.34; p= 0.030), high knowledge (aOR= 2.10; 95% CI= 1.27 to 3.46; p= 0.004), strong social support (aOR=1.73; 95% CI= 1.07 to 2.78; p= 0.020), and the presence of comorbidities (aOR=1.20; 95% CI= 0.67 to 2.16; p= 0.540) improved implementation of self-care practices.Conclusion: Female patients, high knowledge, strong social support, and the presence of comorbidities improve implementation of self-care practices. Keywords: factors, diabetes self-care practices, diabetes mellitus